PENGARUH ASSURANCE TERHADAP LOYALITAS PELANGGAN CORPORATE TIKET MASKAPAI PENERBANGAN DOMESTIK PT. INTERLINK TOURS & TRAVEL BANDUNG (Survey Kepada Pelanggan Corporate Tiket Maskapai Penerbangan Domestik PT. Interlink Tours and Travel Bandung) - Aryanti, Desy; Ahman, Eeng (Universitas Pendidikan Indonesia, 2012)
Travel and tourism in the world is a milestone for the global economy industry today. Tourism is currently standing strong in almost all countries as an industry in their respective countries, including Indonesia. One of the important tourism industry in the implementation of tourism is travel services as tourist facilities required to meet travel. One of the travel services required by tourists is a travel agency. Many travel agents established in the provinces where people often travel potentially that West Java especially in Bandung. In 2011 the number of places of business travels are in Bandung as many as 218. One of the largest travel agency in Bandung is PT. Interlink Tours and Travel. In terms of sales, PT. Interlink Tours and Travel rely more on domestic airline tickets customers in large numbers and repeatedly. In 2011 customers of PT. Interlink Tours and Travel have decreased loyalty. One way PT. Interlink Tours and Travel do to enhance customer loyalty to an airline ticket sales in accordance with the target is to provide quality service to customers with a focus on communication, credibility, security, competence and courtesy. In marketing this is called assurance. Assurance theory used is the theory of the Parasuraman in Ririn Tri Ratnasari (2011:109) and the theory of customer loyalty using the theory Baloglu (2002). The population in this study is the corporate customers of domestic airline tickets in PT. Interlink Tours and Travel Bandung. Sampling technique used is saturated sampling and data analysis technique used is multiple regression. Overview of research on assurance and customer loyalty is in a good position. The results showed simultaneous assurance effect on customer loyalty. However, partially only competence sub variables that influents the loyalty, while the other four sub variables, namely communication, credibility, security and courtesy are no effect on customer loyalty.